Evaluation of Skin Viscoelasticity in Type 1 Neurofibromatosis Patients - Mimoun, N.; Razzouq, N.; Wolkenstein, P.; Moreno, J.C.; Marty, J.P.; Lantieri, L.; Astier, A.; Paul, M. (Skin pharmacology and physiology, 2006)
Neurofibromatosis type 1 (NF1) is a frequent autosomal dominant disease characterized by cutaneous benign tumors called neurofibromas. Surgery takes an important place in managing these skin disorders. However, skin distensibility and softness of NF1 patients quickly offset the surgical benefit. The aim of this study was to determine the rheological behavior of neurofibromas and compare it with healthy skin in an attempt to comprehend what leads to this phenomenon. Thirty patients were admitted to this study. A group of 24 healthy control subjects was also included. The skin elasticity was assessed by a noninvasive in vivo suction device (Cutometer) including 5 consecutive suctions. The assessments were performed on neurofibroma skin, the supposedly healthy skin around neurofibromas and the healthy skin of control subjects. The extensibility at the first and the fifth traction in NF1 patients (neurofibromas and the supposedly healthy skin around it) was significantly different compared to the healthy skin of control subjects. The viscoelastic parameters obtained from the neurofibromas were significantly different in comparison to those obtained from the supposedly healthy skin of NF1 patients and the healthy skin of control subjects. The rheological profiles of the neurofibromas and the apparent healthy skin of NF1 patients demonstrated a hyperextensibility behavior, but in neurofibromas, the skin was unable to return to its initial position at the end of the stretch.